Identity Crisis and Cultural Trauma in Manju Kapur’s Home - Paudel, Dhaneshwar (BMC Research Journal, 2026)
People cannot forget their cultural identity because it always remains in their mind. So, when they make a plan to do new work or live in a new place, they cannot escape from their previous identity. Thus, this paper explores how the characters feel identity and cultural crisis in Manju Kapur’s (2007) Home. When people go to different places and become associated with distinct cultures, they have the nostalgic feeling of their preceding behavior and place. Even the educated people have the trouble to escape from the traditional concept in new society because their conventional thoughts are deeply rooted in their mind. The past identity of them becomes the main obstacle to establish new concepts because they suffer from the long established behavior. The researcher has used Urvashi Butalia’s notion of the conviction of identity and cultural crisis in the paper. Banwari Lal, Sona Gupta, and Nisha Gupta are distressed or disturbed because they have a fragmented mind in a new environment.